Državljanski dnevnik - Luthar, Oto (ZRC SAZU, Založba ZRC, 2011)
Državljanski dnevnik ('Citizen's Diary') is a unique publication bringing thematisations of past and present issues of active citizenship. The authors, four Slovenians and an American, seek to answer the question to what extent are we, as citizens, responsible for the state of public affairs in democratic societies. To do this they reflect on various cases form the period between the Second World War and the end of 20th century.